Aortic intima media thickness in children and adolescents with type 1 diabetes: A systematic review. Issue 4 (21st February 2022) - Gow, Megan L.; Varley, Benjamin J.; Nasir, Reeja F.; Skilton, Michael R.; Craig, Maria E.
Abstract: Aims: Greater aortic intima media thickness (aIMT), a marker of subclinical atherosclerosis, can identify individuals at risk of CVD. This systematic review with meta‐analysis compared aIMT in youth with type 1 diabetes and healthy controls. Methods: A systematic search of published literature (to July 2021) was undertaken using electronic databases MEDLINE, EMBASE, Scopus, CINAHL and AMED. Eligible studies reported aIMT in participants aged <20 years with type 1 diabetes and healthy controls. Meta‐analysis was used to combine outcome data, presented as forest plots. Moderator analysis and metaregression were conducted to identify study and participant characteristics associated with aIMT. Publication bias was assessed by funnel plot inspection. Results: Meta‐analysis of nine studies (n = 1030 with type 1 diabetes and n = 498 healthy control participants) indicated, with high heterogeneity (I 2 98%), that youth with type 1 diabetes have higher aIMT compared with healthy controls (mean difference [95% CIs]: 0.11 [0.04, 0.18] mm, P = 0.003). Factors associated with greater aIMT in type 1 diabetes compared to controls included: use of a phased array probe versus linear array probe; longer diabetes duration; higher insulin dose; higher BMI z score and waist circumference; higher LDL cholesterol; higher triglycerides; and higher diastolic blood pressure. Conclusions: Type 1 diabetes in youth is associated with higher aIMT compared with healthy control individuals. Longer duration of diabetes and major CVD risk factors were also associated with higher aIMT. Together, these findings provide a strong rationale for targeting modifiable risk factors in CVD prevention. Registered in PROSPERO on 8 August 2019 (CRD42019137559).